2020
DOI: 10.1016/j.ygyno.2019.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Off-study utilization of experimental therapies: Analysis of GOG249-eligible cohorts using real world data

Abstract: h i g h l i g h t s Off-study experimental arm utilization of VBT þ CT for patients eligible for GOG 249 significantly increased from 2004-2015. High socioeconomic status and high grade histology were associated with use of VBT þ CT. Providers should exercise caution when using off-study experimental treatments prior to reported results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the subgroup analysis of Chodavadia et al, chemoradiotherapy was found to be associated with improved overall survival rates compared with radiotherapy alone for patients with high-intermediate and high-risk stage IB endometrial carcinomas. However, no overall survival benefits were identified for stages IA or II endometrial carcinomas (enrolling 852 patients with stage IA–II uterine serous carcinoma) 22 . The results of a study by de Boer et al, in which 105 patients with stage IA–III uterine serous carcinoma were enrolled, showed that a significant improvement in overall survival was observed with chemoradiotherapy compared with radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the subgroup analysis of Chodavadia et al, chemoradiotherapy was found to be associated with improved overall survival rates compared with radiotherapy alone for patients with high-intermediate and high-risk stage IB endometrial carcinomas. However, no overall survival benefits were identified for stages IA or II endometrial carcinomas (enrolling 852 patients with stage IA–II uterine serous carcinoma) 22 . The results of a study by de Boer et al, in which 105 patients with stage IA–III uterine serous carcinoma were enrolled, showed that a significant improvement in overall survival was observed with chemoradiotherapy compared with radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Similar RT use trends have also been reported in America using the National Cancer Database (NCDB). Parth A. Chodavadia et al evaluated the off-study use of RT and found the largest increase in VBT + CT use in 2009 and in the year GOG-249 was initiated [ 13 ]. Sara J. Zakem et al demonstrated that the utilization rate of VBT alone was higher than that of pelvic EBRT.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature concerning the administration schedule of adjuvant treatments for EC, most of which report results with respect to advanced stages, excluding intermediate–high- and high-risk EC [ 16 , 17 , 21 , 22 , 23 ]. In contrast, our study includes both initial stages (27.6% FIGO I–II stages) and advanced stages (72.4% FIGO III-IV stages) at high risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, performing RT before CT may lead to progression outside the radiation fields. Therefore, the “sandwich” schedule can be considered as a possible alternative [ 16 , 17 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%